Періоди розвитку польської іншомовної освіти - Загоруйко, Людмила (Studies in Comparative Education, 2014)
У статті охарактеризовано розвиток польської іншомовної освіти в контексті реформування галузі навчання іноземних мов у Західній Європі. Іншомовна освіта розглядається в часово-просторовому вимірі, що синхронізується з розвитком польського суспільства. Першим періодом розвитку іншомовної освіти у Польщі автор виділила 1950–1980-ті роки – період організаційного становлення. Аналізуючи певні політичні трансформації, що зумовили потребу в докорінних змінах польської вищої системи освіти, у тому числі й іншомовної підготовки, автор виділила другий період періодизації – період європейського спрямування (1989–2004). В статье охарактеризовано развитие польского иноязычного образования в контексте реформирования области обучения иностранным языкам в Западной Европе. Иноязычное образование рассматривается в временно-пространственном измерении, что синхронизируется с развитием польского общества. Первым периодом развития иноязычного образования в Польше автор выделила 1950-1980-е годы - период организационного становления. Анализируя определенные политические трансформации, обусловили потребность в коренных изменениях польской высшей системы образования, в том числе и иноязычной подготовки, автор выделила второй период периодизации - период европейского направления (1989-2004). The article describes the development of Polish foreign language education in the context of teaching foreign languages reforming in Western Europe. Foreign language education is seen in a time-spatial dimension that is synchronized with the development of Polish society. This shows that any component of the educational system in the country is covered in the national context of a historical time period and in certain social and political conditions. So, in the early postwar years, there is a serious conflict between the new post-war requirements for teaching foreign languages and obsolete pre-war model of learning. The authors identified the first period of foreign language education in Poland (1950–1980) as the period of organizational development. In this period the main step in developing foreign language education was in 1976 where the Council of the European Community Ministers had adopted the first joint program of educational activities. That Programe provided the following statements: 1) the creation of favorable conditions for general and vocational education of immigrants and their children; 2) the collection and dissemination of information on European education systems; 3) the load of documents and statistics; 4) cooperation in the field of higher education; 5) development of teaching foreign languages; 6) equal access to all levels of education. Different political transformation in that period necessitated a radical change of Polish higher education system, including foreign language training, and marked the beginning of the second period of our periodization - European orientation (1989-2004).